Perceraian Akibat Tingkat Pendidikan (Studi Putusan Pengadilan Agama Tanjung Karang Nomor 2054/Pdt.G/2025/PA.Tnk) - Sherlychaesa Agustine (Jurnal Hukum Lex Generalis, 2025)
The level of education is believed to affect household stability, meaning that the higher a person's level of education, the greater their knowledge about life, so the risk of divorce tends to be lower. However, higher education can also be a bridge to divorce, therefore this study will look at the divorce case of the court Number 2054 / Pdt.G / 2025 / PA.Tnk regarding divorce by talaq. This study uses a normative legal method with descriptive data. Based on the aspect of the form of the decision number 2054 / Pdt.G / 2025 / PA.Tnk has fulfilled all the required structural components containing the Identity of the parties to the case, Chronology of the case, Decision. The type of decision is a default decision. In consideration of the judge granted the applicant's request by issuing a Raj'i divorce.